Attention deficit hyperactivity and autism spectrum disorders in patients with anorectal malformations. (17th September 2021) - Wester, Tomas; Gunnarsdottir, Anna; Skoglund, Charlotte; Svenningsson, Anna
Abstract: Aim: To assess the risk of neurodevelopmental disorders in patients with anorectal malformations compared to controls. Methods: This was a population‐based cohort study including all patients born in Sweden 1997–2012 with anorectal malformation in the Swedish National Patient Register and five matched controls per patient. Anorectal malformation was the exposure. All individuals were evaluated for the outcomes, attention deficit hyperactivity disorder or autism spectrum disorder in the National Patient Register. Data on drugs for attention deficit hyperactivity disorder were retrieved from the Swedish Prescribed Drug Register and used as proxy for attention deficit hyperactivity disorder. Conditional logistic regression was used to calculate odds ratios (OR) and 95% confidence intervals (95% CI). Analyses were adjusted for confounders. Results: Five hundred and fifteen patients with anorectal malformations and 2560 controls were included. Patients with anorectal malformation had a higher risk of attention deficit hyperactivity disorder (OR 3.01 (95% CI, 1.83–4.95)) and autism spectrum disorders (OR 3.07 (95% CI, 1.62–5.79)) compared to the controls. Significantly more patients with anorectal malformation had been prescribed medication for attention deficit hyperactivity disorder compared to controls (OR 2.26 (95% CI 1.33–3.85)). Conclusion: Patients with anorectal malformations have a higher risk of attention deficit hyperactivity disorder and autism spectrum disorders than controls.